Pengaruh Ukuran Perusahaan, Audit Lag dan Financial Distress Terhadap Opini Audit Going Concern - Shelly Gandini Febrianti; Fina Fitriyana (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine and analyze the influence of Firm Size, Audit Lag, and Financial Distress on Going Concern Audit Opinions of companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. This research is a quantitative associative study. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sampling technique used is purposive sampling, resulting in 51 companies selected from a total population of 255. The data used in this study are logistic data obtained from secondary sources through documentation and literature review methods. The data analysis methods include descriptive analysis and logistic regression using Eviews 12. The results of the study show that, simultaneously, Firm Size, Audit Lag, and Financial Distress have a significant effect on Going Concern Audit Opinions. Partially, Firm Size has no significant effect, Audit Lag has a effect, and Financial Distress has a negative effect on Going Concern Audit Opinions during the 2019–2023 period.